2021
DOI: 10.2478/abm-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation therapy for diabetic foot ulcer: a narrative review

Abstract: Diabetes mellitus is a chronic metabolic disease associated with high cardiovascular risk. A vascular complication of diabetes is foot ulcers. Diabetic foot ulcers are prevalent and substantially reduce the quality of life of patients who have them. Currently, diabetic foot ulcer is a major problem for wound care specialists, and its treatment requires considerable health care resources. So far, various therapeutic modalities have been proposed to treat diabetic foot ulcers and one of them is stem cell-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Previous studies showed intra-arterial and intra-muscular injection on chronic limb ischemia results in a better micro-perfusion (69). However, intra-arterial injection may not increase the efficacy of treatment because of the lack of perfusion in diabetic peri-wound area (70). As for the clinical application of ASCs, Moon et al and Carstens et al injected autologous adipose-derived stromal vascular fraction (SVF) cells to diabetic patients, which contains ASCs and stromal cells essential for epidermal reconstruction (64,65).…”
Section: Clinical Indications and Usage Of Ascsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies showed intra-arterial and intra-muscular injection on chronic limb ischemia results in a better micro-perfusion (69). However, intra-arterial injection may not increase the efficacy of treatment because of the lack of perfusion in diabetic peri-wound area (70). As for the clinical application of ASCs, Moon et al and Carstens et al injected autologous adipose-derived stromal vascular fraction (SVF) cells to diabetic patients, which contains ASCs and stromal cells essential for epidermal reconstruction (64,65).…”
Section: Clinical Indications and Usage Of Ascsmentioning
confidence: 98%
“…Previous studies showed intra-arterial and intra-muscular injection on chronic limb ischemia results in a better micro-perfusion ( 69 ). However, intra-arterial injection may not increase the efficacy of treatment because of the lack of perfusion in diabetic peri-wound area ( 70 ). As for the clinical application of ASCs, Moon et al.…”
Section: Clinical Progress Of Ascs In Treating Diabetic Woundsmentioning
confidence: 99%
“…Additionally, enhanced wound healing in a murine model of DFUs using human amniotic MSCs, the micronized amniotic membrane containing human amniotic epithelial cells, human placental MSC, collagen gels containing embryonic fetal liver MSCs, and collagen hydrogel scaffold to deliver human fetal aortic MSCs has also been reported. Moreover, the use of embryonic stem cells, induced pluripotent stem cells, and granulocyte-colony stimulating factors stimulating bone marrow to mobilize endothelial progenitor cells at the wound site, have also been documented and reviewed [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Stem Cells and Angiogenesis In Dfusmentioning
confidence: 99%
“…Using stem cells for wound healing is another promising approach. Multiple articles in the literature have reviewed the mechanism and the role of stem cells in enhancing wound healing [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Hence, this review focuses on the role of stem cells in promoting angiogenesis to enhance wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, it is imperative to develop an efficacious therapeutic approach to settle this problem. In clinical, several strategies such as wound dressing, 3,4 cell therapy, 5 and drug delivery 6 are applied to improve wound healing. However, the complicated wound condition requires specific wound management and coordinated treatment, which still remains a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%